Evaluation of rotation thrombelastography for the diagnosis of hyperfibrinolysis in trauma patients - Levrat, A; Gros, A; Rugeri, L; Inaba, K; Floccard, B; Negrier, C; David, J-S (British journal of anaesthesia : BJA, 2008)
Blood loss and uncontrollable bleeding are major factors affecting survival in trauma patients. Because treatment with antifibrinolytic drugs may be effective, early detection of hyperfibrinolysis with rotation thrombelastography (ROTEM may be beneficial. Eighty-seven trauma patients were included in this prospective observational study. Blood samples were collected at admission. After in vitro activation with tissue factor (EXTEM) and inhibition with aprotinin (APTEM), ROTEM parameters including maximal clot firmness (MCF) and clot lysis index at 30 min (CLI(30)) were determined. Hyperfibrinolysis was defined as a euglobulin lysis time (ELT) <90 min. Threshold for ROTEM parameters were determined with receiver-operating characteristic curves (ROC) analysis according to the ELT results. ELT was determined in a subgroup of 23 patients. In this group of patients, ROC analysis showed that for a threshold of 18 mm (MCF-EXTEM), 71% (CLI(30)) and 7% (increase of MCF-APTEM), sensitivity was, respectively, 100%, 75%, and 80% with a specificity of 100%. With the application of these thresholds to the whole trauma cohort, ROTEM analysis detected hyperfibrinolysis in five patients [6%, 95% confidence interval (CI): 2-13%]. As expected, patients with hyperfibrinolysis were more severely injured (median Injury Severity Score: 75 vs 20, P<0.05), had greater coagulation abnormalities [international normalized ratio (INR): 8.2 vs 1.3, P<0.05; fibrinogen: 0.0 vs 2.2 g litre(-1), P<0.05], and a higher mortality rate (100%, CI: 48-100% vs 11% CI: 5-20%, P<0.05). ROTEM provided rapid and accurate detection of hyperfibrinolysis in severely injured trauma patients.